Frameworks of Regulation: Evidence, Knowledge and Judgement in Inspection - Ozga, Jenny (2014)
This issue of Sisyphus draws on work in the research project ‘Governing By inspection: school inspection and education governance in England, Scotland and Sweden’. That research seeks to fill a gap in the literature on the governing of education by examining the ways in which inspection regimes may be understood as governing education-in this case in the three national education systems of Sweden, England and Scotland. (...)